2016
DOI: 10.1016/j.colsurfb.2015.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Complex film of chitosan and carboxymethyl cellulose nanofibers

Abstract: A polymer film composed of a mixture of chitosan (Ch) and carboxymethyl cellulose sodium salt (CMC) nanofibers was deposited on a glass surface. The thin film of the Ch-CMC mixture obtained was stable, and fibroblast adhesion to the film was lowest when the weight ratio of Ch to CMC was 4:6. The ζ-potential and contact angle of the mixture film indicated that a polyion complex of Ch and CMC was formed. The mechanical strength of the film composed of Ch-CMC nanofiber complexes was much higher than that of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 44 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Hence, biopolymers are considered promising materials with the advantages of renewability, degradability, edibility, and biocompatibility, for example, the lyocell fiber [7] and chitosan/ellagic acid films [1]. Moreover, biopolymers can be used as carriers of preservatives, antioxidants, and other substances to protect and improve food quality [8]. The edible film (packaging material) prepared by using a biopolymer is being developed rapidly because of its biodegradability and potential barrier properties to moisture and gases and reduced environmental pollution caused by the application of traditional plastic packaging [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, biopolymers are considered promising materials with the advantages of renewability, degradability, edibility, and biocompatibility, for example, the lyocell fiber [7] and chitosan/ellagic acid films [1]. Moreover, biopolymers can be used as carriers of preservatives, antioxidants, and other substances to protect and improve food quality [8]. The edible film (packaging material) prepared by using a biopolymer is being developed rapidly because of its biodegradability and potential barrier properties to moisture and gases and reduced environmental pollution caused by the application of traditional plastic packaging [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CS, which is characterized by its long-lasting action, high adherence, and antibacterial properties, is an optimal additive for formulating composite films for practical applications. Kawasaki et al [15] prepared a CS/CMC nanofiber composite film, and demonstrated that the addition of CS effectively inhibited the growth and adhesion of bacteria, showing a vast potential for biomedical material applications. Further, Noshirvani et al [16] studied the influence of cinnamon and ginger essential oils on the physical and chemical properties of CS/CMC films.…”
Section: Introductionmentioning
confidence: 99%
“…2D CMC nanofibrous wound dressings have been extensively studied due to their microstructure similarity to intact skin tissue and extracellular matrix (ECM) and their high potential as drug carriers, liquid absorbents, and moisturizers. Various strategies can fabricate CMC nanofiber dressings, including ultrasonication, casting, freeze-drying, and electrospinning [91,104,105]. Electrospinning is the most widely used CMC nanofiber dressing fabrication technique due to its low costs, green fabrication, simplicity, reliability, and versatility [87,92,106,107].…”
Section: Cmc-based Nanofibersmentioning
confidence: 99%